The Influence of Discounts, Free Shipping, and Online Reviews on Purchase Decisions with Buying Interest As an Intervening Variable Among Shopee Consumers In Surabaya (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to examine and analyze the influence of Discount, Free Shipping, and Online Review on Purchase Decision with Buying Interest as an intervening variable among Shopee consumers in Surabaya. The research method employed is quantitative with an explanatory approach. Data were collected through questionnaires from 104 respondents selected using a purposive sampling technique, with criteria including residency in Surabaya and having conducted transactions on Shopee. Data analysis was performed using Path Analysis via SPSS 27 software. The results indicate that Discount, Free Shipping, and Online Review have a positive and significant influence on Buying Interest both partially and simultaneously. Directly, the three independent variables also significantly influence the Purchase Decision. The Sobel Test results confirm that Buying Interest significantly mediates the influence of Discount, Free Shipping, and Online Review on the Purchase Decision. Discount was found to be the most dominant variable in influencing the consumer's final decision. These findings emphasize that economic incentives and the credibility of digital information are effective in driving tangible transactions if they are capable of generating a psychological drive in the form of buying interest first.